EFEKTIVITAS Aspergillus niger DAN Penicillium sp. DALAM MENINGKATKAN KETERSEDIAAN FOSFAT DAN PERTUMBUHAN TANAMAN JAGUNG PADA TANAH ANDISO - Putri Juli Artha; Hardy Guchi Hardy Guchi; Posma Marbun Posma Marbun (Universitas Sumatera Utara, 2013)
This research topic is the effectiveness of Aspergillus niger and Penicillium sp. in increasingphosphate and growth of corn on Andisol. The objective is to compare the effect of Aspergillusniger application with Penicillium sp. in increasing phosphate and corn growth on Andisol.Andisols material was taken from Kuta Rakyat Village, Namanteran Subdistrict, Karo District. Thisresearch was conducted at green house, Soil Biology Laboratory, and Soil Fertility and ChemistryLaboratory. The design used was non factorial blocky randomized which consists of seventreatments and four replications, they are M0 (kontrol), MA1 (Aspergillus niger 8 mL), MA2(Aspergillus niger 17 mL), MA3 (Aspergillus niger 25 mL), MP4 (Penicillium sp. 10 mL), MP5(Penicillium sp. 18 mL), MP6 (Penicillium sp. 30 mL). Parameters measured in this experiment aresoil pH, soil available-P, plant P absorption, shoot dry weights, and root dry weights.The results of this research showed that the application of Aspergillus niger and Penicillium sp. nonsignificantly affected available P, P-uptake, soil pH, and shoot dry weights, but significantlyaffected root dry weights and diameter of stem.Keywords : aspergillus niger, penicillium sp., Andisols